Sexual Assault and Sexual Harassment in the U.S. Military Volume 4. Investigations of Potential Bias in Estimates from the 2014 RAND Military Workplace Study - Morral, Andrew R. (Research Reports, 2016)
The Department of Defense Sexual Assault Prevention and Response Office asked the RAND Corporation to independently assess rates of sexual assault, sexual harassment, and gender discrimination in the military. This volume presents the results of methodological investigations into sources of potential bias in estimates produced from the 2014 RAND Military Workplace Study for active- and reserve-component members in the U.S. military.